Pembentukan Kata Majemuk Karakter Marvel pada Marvel.com (Pendekatan Morfologi) - Rahayu, Anita; Wibowo, Agus Hari (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The research focused on the analysis of the types and the reasons for the compounding behind the names of Marvel characters on marvel.com. Marvel Comics' character names were the possible linguistics media that created identities for the superheroes and villains that intrigued audiences worldwide. The factors behind the merging phenomenon, according to (Lieber, 2021), are semantic transparency, phonological form, and morphological structure. The types of compounds in this research were exocentric and endocentric, while the reasons behind the compounding were examined. The research applied a descriptive qualitative design with a morphological approach and the analysis employs Spradley's method, specifically ethnographic analysis. The results showed 18 instances of compounding, with 9 of them belonging to endocentric compounds and 8 to exocentric compounds.